2020
DOI: 10.1038/s41467-020-16019-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptional networks in differentiating preadipocytes suggest drivers associated with tissue heterogeneity

Abstract: White adipose tissue plays an important role in physiological homeostasis and metabolic disease. Different fat depots have distinct metabolic and inflammatory profiles and are differentially associated with disease risk. It is unclear whether these differences are intrinsic to the pre-differentiated stage. Using single-cell RNA sequencing, a unique network methodology and a data integration technique, we predict metabolic phenotypes in differentiating cells. Single-cell RNA-seq profiles of human preadipocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Previous work using scRNA-seq to determine molecular changes during adipogenesis (day 1–7) in vitro found that at day 3 the cell clustering was mainly driven by ECM genes, and at day 7 the core matrisome was one of the top ten most differentially expressed gene ontology terms [34] . Beyond development, planarian scRNA-seq revealed that muscles produce most of the matrisome, and inhibiting one key matrisome gene (hemicentin) resulted in severe epidermal ruffling and displacement of cells during homeostatic tissue turnover, suggesting an important role for tissue regeneration [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work using scRNA-seq to determine molecular changes during adipogenesis (day 1–7) in vitro found that at day 3 the cell clustering was mainly driven by ECM genes, and at day 7 the core matrisome was one of the top ten most differentially expressed gene ontology terms [34] . Beyond development, planarian scRNA-seq revealed that muscles produce most of the matrisome, and inhibiting one key matrisome gene (hemicentin) resulted in severe epidermal ruffling and displacement of cells during homeostatic tissue turnover, suggesting an important role for tissue regeneration [28] .…”
Section: Discussionmentioning
confidence: 99%
“…This is difficult because the emergence of beige adipocytes in subcutaneous adipose tissue is heterogeneous and occurs in pockets surrounding vasculature [ 82 ]. Moreover, the advent of single cell and single nuclei RNA sequencing, as well as the refinement of cold stress conditions, have demonstrated that there are numerous subtypes of beige adipocyte that have differences in glycolytic capacity and cellular origin [ 83 , 84 , 85 , 86 ]. These studies have also revealed lipid signaling between beige adipocytes and resident macrophages that regulates the thermogenic response [ 84 , 87 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Previous work using scRNA-seq to determine molecular changes during adipogenesis (day 1-7) in vitro found that at day 3 the cell clustering was mainly driven by ECM genes, and at day 7 the core matrisome was one of the top ten most differentially expressed gene ontology terms [31]. Beyond development, planarian scRNA-seq revealed that muscles produce most of the matrisome, and inhibiting one key matrisome gene (hemicentin) resulted in severe epidermal ruffling and displacement of cells during homeostatic tissue turnover, suggesting an important role for tissue regeneration [26].…”
Section: Discussionmentioning
confidence: 99%